3D Numerical Simulation of Seamless Pipe Piercing Process by Fluid-Structure Interaction Method - Topa Ameen; Kim Do Kyun; Kim Youngtae (MATEC Web of Conferences, 2018)
Seamless pipes are produced using piercing rolling process in which round bars are fed between two rolls and pierced by stationary plug. During this process, the material undergoes severe deformation which renders it impractical to perform the numerical simulations with conventional finite element methods. In this paper, three dimensional numerical simulations of the piercing process are performed with Fluid-Structure Interaction (FSI) Method using Arbitrary Lagrangian-Eulerian (ALE) Formulation with LS DYNA software. The results of numerical simulations agree with experimental data of Plasticine workpiece and the validity of the analysis method is confirmed.